Impacts of Implementing the Learning Policy on Vocational Higher Education in Post Covid-19 Pandemic - Romy Hermawan; M. Daniel Septian; Hayat Hayat (STAI Hubbulwathan Duri, 2022)
This study aimed to describe the influences of learning policies within the period of vocational higher education after the Covid-19 pandemic. The field research design applied the quantitative approach. The research population, 5.915 respondents, came from elements of the academic community at the Vocational Education Program, Brawijaya University, Malang, and the Vocational Faculty, Airlangga University, Surabaya. Then, the sampling technique determined 98 samples based on the Stratified Random Sampling approach. Data collection techniques were supported by questionnaires, documentation, and interviews. In order to facilitate the analysis, we used parametric inference statistical analysis techniques to test the validity and reliability. The results of the validity test through correlation (Pearson Correlation Coefficient) and the reliability test with the Cronbach Alpha method (Cronbach's Alpha) showed that all question items had been proven to be valid based on the sig value 0.05. From 18 items, the Cronbach alpha value was 0.785. As it was more than 0.6, the questionnaire was valid. Also, the reliability test of 16 items obtained from Cronbach's alpha value was 0.838. It was more than 0.6, meaning that the questionnaire was valid. The correlation value between items 1-18 had a fairly high correlation, and the view of the question value sig. 2 tailed overall was 0.05, meaning that each question item was valid. The findings from this study indicated that the existence of learning policies has a significant influence on the vocational learning process during the Covid-19 pandemic. This study recommends that in the post-Covid-19 pandemic, educational policies in higher education units of vocational type are more adaptive to digital-based learning by strengthening health principles and protocols.